2023
DOI: 10.3390/buildings13071630
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanographite Conductive Concrete Mixed with Magnetite Sand Excited by Different Alkali Activators and Their Combinations on the Properties of Conductive Concrete

Abstract: In order to obtain conductive concrete with good electrical conductivity and good mechanical properties, nanographite and magnetite sand excited by different activators and their combinations are added to ordinary concrete to obtain high quality and efficient conductive concrete. The optimal mixture ratio of alkali-excited conductive concrete and the effects of different activators and their combinations on the mechanics and electrical conductivity of concrete were studied. The microstructure of alkali-excited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Considerations have also examined the sedimentation process in ferrofluids, utilized fluorophore molecules for dual-channel fluorescence chemo sensing, and employed MOFs as probes for water content measurement. Additionally, research has explored terahertz meta sensors for refractive index sensing and molecular identification, proposed linear free energy relationships for predicting partition coefficients in organic compounds, and studied the properties of conductive concrete mixed with nano graphite and magnetite sand [48][49][50][51].…”
Section: Effect Of High-frequency Traveling-wave Magnetic Field Direc...mentioning
confidence: 99%
“…Considerations have also examined the sedimentation process in ferrofluids, utilized fluorophore molecules for dual-channel fluorescence chemo sensing, and employed MOFs as probes for water content measurement. Additionally, research has explored terahertz meta sensors for refractive index sensing and molecular identification, proposed linear free energy relationships for predicting partition coefficients in organic compounds, and studied the properties of conductive concrete mixed with nano graphite and magnetite sand [48][49][50][51].…”
Section: Effect Of High-frequency Traveling-wave Magnetic Field Direc...mentioning
confidence: 99%
“…4–8 There are also first reports on implementing magnetite nanoparticles to improve the mechanical stability of conductive concrete. 9…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a comprehensive survey has been conducted and the results demonstrated that alkali-activated binding materials have high strength, low carbon content, good frost resistance, etc. [58,59]. Researchers acknowledged the use of geopolymer in retaining walls, boundary blocks, pavements, water tanks, road ramps, and precast beams.…”
Section: Introductionmentioning
confidence: 99%